2020
DOI: 10.3390/ijerph17082926
|View full text |Cite
|
Sign up to set email alerts
|

Association between Passive Smoking from the Mother and Pediatric Crohn’s Disease: A Japanese Multicenter Study

Abstract: Smoking is a risk factor for adult-onset Crohn’s disease (CD). Although passive smoking from family members is a major concern, especially in pediatric CD, the number of existing epidemiological studies is limited. This multicenter case–control study aimed to assess the effects of familial smoking on pediatric CD. We examined 22 pediatric CD cases and 135 controls. The subjects’ mothers were given a self-administered questionnaire about family smoking before disease onset in the CD group or the corresponding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…When mothers who were also smokers were studied (passive maternal smoking), an increase in periodontal pathogens such as Campylobacter and Fusobacterium were uniquely noted in the predentate microbiomes of their offspring. These are important to emphasize because they are also known IBD pathobionts, and a recent multicenter study found that passive maternal smoking had a dose-dependent association with the development of pediatric IBD (170). Additionally, maternal smoking habits in the perinatal period have been associated with developing IBD in their offspring (odds ratios of 5.32 for CD; 3.02 for UC) when matched to unexposed controls, and we hypothesize that these oral microbial alterations may play an active role in the exacerbation or acceleration of IBD.…”
Section: Oral Microbiomial Development: Oral Mucosa Subgingiva and Sa...mentioning
confidence: 99%
“…When mothers who were also smokers were studied (passive maternal smoking), an increase in periodontal pathogens such as Campylobacter and Fusobacterium were uniquely noted in the predentate microbiomes of their offspring. These are important to emphasize because they are also known IBD pathobionts, and a recent multicenter study found that passive maternal smoking had a dose-dependent association with the development of pediatric IBD (170). Additionally, maternal smoking habits in the perinatal period have been associated with developing IBD in their offspring (odds ratios of 5.32 for CD; 3.02 for UC) when matched to unexposed controls, and we hypothesize that these oral microbial alterations may play an active role in the exacerbation or acceleration of IBD.…”
Section: Oral Microbiomial Development: Oral Mucosa Subgingiva and Sa...mentioning
confidence: 99%
“…Further, our finding of neither a clinically nor statistically significant association between childhood passive tobacco smoking exposure and CD is consistent with existing research, where childhood passive smoking exposure has been consistently found to have no association with CD. 8 , 25 , 26 Overall, this study suggests a detrimental effect of adult smoking on the risk of CD in a previously understudied population in the Middle East. These findings, together with the existing literature, suggest a need for smoking cessation initiatives in populations at high risk of CD in the region, where smoking is prevalent, particularly amongst men, for whom it is culturally acceptable.…”
Section: Discussionmentioning
confidence: 61%
“… 7–9 The resulting dysbiosis is thus part of the pathogenesis of the disease and is maintained by the inflammatory response at the same time. Environmental triggers include Western dietary habits, 10 active and passive smoking, 11–13 use of antibiotics, 14 , 15 NSAID 16 , 17 and oral contraceptives. 18 …”
Section: Introductionmentioning
confidence: 99%